Annual report 2010 - (:unkn) unknown (Office for Official Publications of the European Communities, 2011)
"The Annual report 2010 is structured according to Cedefop's work programme 2010 and reflects the medium-term priorities for the period 2009-11: informing European VET policy; interpreting European trends in and challenges for skills, competences and learning; assessing VET benefits; and raising the profile of VET. It provides a clear overview of achievements compared to set objectives. [...] The report also refers to further developments of Cedefop's management and administration. Organisational developments, partly because of personnel changes at Director level, focus on streamlining and increasing the efficiency of administrative procedures, and further improvements by implementing the auditors' recommendations and actions devised in response to Cedefop's risk management plan dominated respective activities in 2010." (Hrsg., BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; I 1.5 Internationale Organisationen & Institutionen; I 2.2 Europa; CEDEFOP; Berufsbildungsforschung; EU-Bildungspolitik; Europäische Union; 2010